Caribou calf deaths from intraspecific strife — a debatable diagnosis - Miller, Frank L.; Gunn, Anne (Rangifer, 1986)
led to the deaths of several newborn barren-ground caribou (Rangifer tarandus groenlandicus) calves within a short period of time and on a small area. This event took place during calving in June 1958 on the calving ground of the Beverly caribou herd in the Northwest Territories. The lack of other examples of multiple deaths of newborn caribou calves from intraspecific strife and our findings on the same calving ground during a study of calf mortality in June 1981, 1982, and 1983 and a study of cow-calf behaviour in June 1981 and 1982 cause us to question the published explanation. As we rarely saw aggressive behaviour among cows and newborn calves that involved actual physical contact and none that resulted in injury or death and because we found instances of multiple killings of calves by wolves {Canis lupus) we suggest that a probable alternative explanation of the 1958 findings is surplus killing by wolves. Most importantly, only direct observation of an event allows separation of a death caused by injuries due to intraspecific strife from a death caused by accidental injuries.
Keywords: caribou; calf; mortality; intraspecific strife; Northwest Territories; Canada